Adjustment in EMU : a model-based analysis of country experiences - Langedijk, Sven.; Roeger, Werner; European Commission : Directorate-General for Economic and Financial Affairs (Brussels- Belgium: European Comission: Directorate-General for Economic and Financial Affairs, 2007)
This paper uses a two-country-three-sector DSGE model to analyse adjustment in the Euro area. A particular distinction is made between tradeables and non tradeables and non tradeables are further disaggregated into housing and services. The experience of six countries which have shown strong divergences in the early years of the euro area, namely Germany, Ireland, Italy, the Netherlands, Portugal and Spain is analysed. The framework allows replication of actual developments in euro-area Member States using a model that is inherently stable. It is found that to a large extent, the diverging growth and inflation developments and current account shifts can be attributed to one-off adjustment to EMU which broadly seems to have run its course. The absence of an exchange risk premium in EMU allows an increase in capital mobility resulting in a lower correlation between domestic savings and investment. Increased capital mobility seems to have been an important driving force behind the current account dynamics. Due to the absence of risk premia, investment - and especially housing investment - responds strongly to exogenous shocks.
Economic Papers